Analysis of the Quality and Quantity of Well Water in Pulau Osi Hamlet, West Seram District, West Seram Regency - Rinda, Rinda; Salakory, Melianus; Leuwol, Ferdinand Salomo (Program Studi Pendidikan Geografi FKIP Universitas Pattimura, 2022)
Education is one of the things that needs to be considered to create the next generation of Indonesians who have an intelligent mindset and good concepts in dealing with global challenges. The problem plaguing the world of education is a disease caused by a virus known as Covid-19. The approach that can be taken so that education can be carried out even with the conditions of the Covid-19 pandemic is blended learning. This study aimed to examine how blended learning is used in classes at SMA Negeri 5 Central Maluku. The method used is a qualitative research approach used qualitatively. The results of this study are the use of blended learning because online learning is only sometimes the best choice, and a face-to-face learning process is needed. Instructors need to be better at creating engaging learning materials to make the online learning environment attractive. RPP made online must also be considered by the teacher